THE EFFECT OF COMPENSATION AND JOB CHARACTERISTICS ON PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT (A STUDY OF PEKALONGAN CITY GOVERNMENT EMPLOYEES) - Dwi Pardianto; Endang Tjahjaningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the direct and indirect effects of compensation and job characteristics on employee performance, with organizational commitment as a mediating variable. The study used a quantitative approach with a survey method. Data were collected through a questionnaire with a Likert scale of 1–7 and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and mediation tests (Sobel test). The results showed that compensation had no effect on employee performance, while job characteristics had a positive and significant effect on employee performance. Organizational commitment was shown to partially mediate this relationship. The implication is that improving fair compensation systems and effective job design can strengthen employee commitment and improve public sector performance.